Alcoholic chlorhexidine skin preparation or triclosan-coated sutures to reduce surgical site infection: a systematic review and meta-analysis of high-quality randomised controlled trials. Issue 8 (August 2022) - ,; Ademuyiwa, Adesoji O.; Adisa, Adewale O.; Bach, Simon; Bhangu, Aneel; Harrison, Ewen; Ingabire, JC Allen; Haque, Parvez D; Ismail, Lawani; Glasbey, James; Ghosh, Dhruva; Kadir, Bryar; et al.
Summary: Background: WHO and the UK's National Institute for Health and Care Excellence recommend alcoholic chlorhexidine skin preparation and triclosan-coated sutures to prevent surgical site infections (SSIs). Existing meta-analyses that include studies at high risk of bias, combined with the recent publication of large, randomised trials, justify an updated meta-analysis of high-quality randomised controlled trials (RCTs). We aimed to test the rates of SSI according to skin preparation solutions (ie, alcoholic chlorhexidine vs aqueous povidone-iodine) and types of sutures (ie, coated vs uncoated). Methods: In this systematic review and meta-analysis, we searched MEDLINE, Embase, Pubmed, and Cochrane Library databases, with no language restrictions, to identify high-quality RCTs testing either alcoholic chlorhexidine skin preparation ( vs aqueous povidone-iodine) or triclosan-coated sutures ( vs uncoated sutures), or both, published from database inception to Sept 1, 2021. Patients who received clean-contaminated, contaminated, or dirty surgery were included. We predefined the characteristics of a high-quality trial through an expert consensus process to develop an enhanced Cochrane risk of bias-2 tool specifically for RCTs with a primary outcome of SSI. Data were extracted from published reports. Meta-analysis was performed using a random-effects model and heterogeneity was assessed using the I 2 statistic. This systematic review and meta-analysis was prospectively registered in PROSPERO, CRD42021267220. Findings: Of 942 studies identified, 933 were excluded. Four high-quality RCTs (n=7467 patients) were included that tested alcoholic chlorhexidine. No significant difference in SSI rates was noted between alcoholic chlorhexidine and aqueous povidone-iodine (17·9% [667 of 3723 patients] vs 19·8% [740 of 3744 patients]; odds ratio 0·84 [95% CI 0·65–1·06]; p=0·21, I 2 =53·1%). Five high-quality RCTs were included that tested triclosan-coated sutures (n=8619 patients), with no significant difference noted between triclosan-coated and uncoated sutures (16·8% [733 of 4360 patients] vs 18·4% [784 of 4259 patients]; OR 0·90 [95% CI 0·74–1·09]; p=0·29, I 2 =36·4%). Interpretation: Contrary to previous meta-analyses, this study did not show a benefit from either alcoholic chlorhexidine skin preparation or triclosan-coated sutures, both of which are more expensive than other readily available alternatives. Global and national guidance should be reconsidered to remove recommendations for their routine use. Funding: National Institute for Health Research (NIHR) Global Health Research Unit.